Thoughts about eating, weight and shape in anorexia nervosa and bulimia nervosa. - Cooper, M; Fairburn, C (1992)
Concurrent verbalisation and a self-report questionnaire were used to investigate self-statements in patients with anorexia nervosa, patients with bulimia nervosa, two groups of dieters and non-dieting controls. Thoughts were collected while subjects performed three behavioural tasks, looking at themselves in a full-length mirror, weighing themselves and eating a chocolate covered mint. Both groups of patients had more negative thoughts related to eating, weight and shape than those in the three control groups. In addition, patients with anorexia nervosa showed a greater concern with eating while patients with bulimia nervosa showed a greater concern with weight and appearance. Differences were found between the patients and non-dieting controls using both methods but the self-report questionnaire was less sensitive than concurrent verbalisation to differences between the patients and dieters. Implications of the findings for cognitive-behavioural treatments of the two disorders are discussed.